Penguatan Literasi Energi Terbarukan Model Sel Bahan Bakar Hidrogen bagi Guru MGMP Kimia DKI Jakarta - Afrizal Afrizal; Hayyun Lisdiana; Roni Adi Wijaya; Fitri Ramadhani; Siti Azizah; Laurensia Laurensia; Imam Hanafi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to enhance renewable energy literacy and improve the skills of chemistry teachers at Madrasah Aliyah (MA) in DKI Jakarta in developing a hydrogen fuel cell model based on polymer electrolyte membrane (PEMFC) technology. The training was conducted in three stages: preliminary, implementation, and evaluation. The initial stage involved a needs analysis and data collection on teachers’ understanding of fuel cell technology. The implementation stage consisted of lectures, discussions, simulations, assignments, and direct observation of participants’ practical skills in designing the fuel cell model. The evaluation stage assessed the training materials, instructors, and participants to determine the program’s effectiveness. The results showed a significant improvement in teachers’ conceptual understanding and practical competence in integrating hydrogen fuel cell technology into chemistry learning. This program is expected to foster innovative teachers capable of utilising renewable energy technology in classroom practice and improving the quality of students’ academic assessment.